Detection of dis-bond between honeycomb and composite facesheet of an Inner Fixed Structure bond panel of a jet engine nacelle using infrared thermographic techniques. Issue 1 (1st January 2022) - Kidangan, Renil Thomas; Krishnamurthy, Chitti Venkata; Balasubramaniam, Krishnan
ABSTRACT: The Inner Fixed Structure (IFS) bond panel is a honeycomb sandwich panel with CFRP facesheet and a heat shield on one side, and a perforated CFRP facesheet on the other side, of a jet engine nacelle. It is subjected to extreme temperature on both sides which damages the inner epoxy adhesive bond between the facesheet and the honeycomb core. Accessibility to this layer for non-destructive evaluation is extremely challenging using conventional methods. This work proposes active thermography techniques such as flash thermography and induction thermography for accessing the inner layer. The infrared camera utilises the perforations in the facesheet of the IFS bond panel, which is used for attenuating the engine noise, for imaging the defects. However, flash thermography requires the removal of the thermal insulation layer for the inspection, whereas induction thermography can be performed without any modifications to the structure. The minimum detectable dis-bond size using these techniques is restricted to the spacing between the perforations on the facesheet. A numerical model has developed for induction thermography to optimise the excitation frequency that can produce reasonable thermal contrast at the inner facesheet and minimum temperature rise on the intermediate stainless-steel thin sheet that covers the thermal insulation layer.